ANALYSIS OF THE INTERPRETATION OF THE SEA IN THE SPONGEBOB CARTOON - Pen Siau Hong; Assaidatul Husna (JURNAL RUPA MATRA, 2024)
This analysis aims to highlight the social message related to marine pollution conveyed through the cartoon "Spongebob SquarePants" using a qualitative approach employing semiotic analysis. The study will delve into the symbols, objects, and visual representations associated with the ocean in the cartoon. The anticipated outcome of this analysis is to provide insights into how entertainment media like cartoons can influence understanding and awareness of environmental issues such as marine pollution, serving as a basis for further research on the role of media in shaping attitudes and actions towards environmental issues.